2019
DOI: 10.3892/etm.2019.7223
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine improves diabetic retinopathy via the MAPK/ERK pathway

Abstract: Diabetic retinopathy (DR) is one of the most common causes of blindness in developed countries. Due to its asymptomatic onset and progressive disease course, DR is typically diagnosed at a late stage when treatment options are limited and therefore often results in irreversible blindness. Studies have demonstrated that carnosine may prevent and treat DR. In a previous study, the positive effect of carnosine on DR was determined and it was revealed that there may be an association between carnosine and the mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
10
0
4
Order By: Relevance
“…Members of the Mitogen-activated Protein Kinases ( MAPKs ) superfamily are important downstream signaling molecules of PAKs [ 50 , 51 ]. MAPKs are abundant in eukaryotic cells, which can transmit extracellular signals to the nucleus and regulate various physiological and biochemical processes in cells [ 52 ]. As a member of MAPK signaling pathway, MAPK8 , also known as JNK, JNK1 and SAPK1 , participates in many biological and molecular processes, such as cell proliferation, differentiation and apoptosis [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Mitogen-activated Protein Kinases ( MAPKs ) superfamily are important downstream signaling molecules of PAKs [ 50 , 51 ]. MAPKs are abundant in eukaryotic cells, which can transmit extracellular signals to the nucleus and regulate various physiological and biochemical processes in cells [ 52 ]. As a member of MAPK signaling pathway, MAPK8 , also known as JNK, JNK1 and SAPK1 , participates in many biological and molecular processes, such as cell proliferation, differentiation and apoptosis [ 53 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is the study by Y Guo et al that demonstrated how diabetic retinopathy was reversed in rats after administration of carnosine. Moreover, glucose uptake in skeletal muscle cells was enhanced, which suggested reversal of glucolipotoxicity [ 64 ]. They also highlighted that this reversal was facilitated by the MAPK/ERK pathway, which is a pathway implicated in various pathogenetic mechanisms.…”
Section: Management Of Metabolic Disorders Using Rcsmentioning
confidence: 99%
“…Bu çalışma ile diyabetik komplikasyonları o nleme ve tedavi etmede potansiyel çoklu koruyucu olduğ u ifade edilmiştir (44). Karnozinin diyabetik retinopatiyi (DR) o nleyebileceğ ini ve tedavi edebileceğ i du şu nu lerek diyabetik sıçanlar u zerinde yapılan çalışmada mu dahale ğrubuna 25 mcmol/L karnozin verilerek mitojen -aktive olmuş protein kinaz (MAPK)/hu cre dışı sinyale bağ lı kinaz (ERK) sinyal yolunun aktivasyonunun baskılandığ ı ğo ru lmu ştu r. Bu nedenle karnozinin DR'yi o nleme ve tedavi etmede o nemli bir rol oynayabileceğ i ifade edilmiştir (45). Diyabetik nefropati, kronik bo brek yetmezliğ ine yol açabilecek diyabetin o nemli bir komplikasyonudur.…”
Section: Bilişsel Fonksiyonlara Ve Depresyona Etkisiunclassified